Investigation of cutting parameter and machine tool vibration effects using regression analysis to enhance part dimensional accuracy - Ab Rahman, Mahmood; Mohamad, Minhat; Halim, Isa; Baharudin, Abu Bakar (Trans Tech Publications, Switzerland, 2014)
Dimensional accuracy plays important criteria in producing high quality machined parts. This is a big challenge to manufacturers of precision components to produce good quality parts with minimum manufacturing error. The focus of this paper is to study the influence of the machine tool rigidity and cutting parameters on dimensional accuracy in turning operation. A method was prepared for identifying the factors effecting dimensional accuracy in a turning process. Experimental setup involved computerized numerical control (CNC) lathe machine, with VBMT 160404 carbide insert and mild steel, as cutting tool and workpiece respectively. The statistical analysis was used for analyzing and determining the accuracy of experimental data through Minitab statistical software. The regressions model was developed. The developed regression model could be used to predict the dimensional precision of the parts based on machine tool vibration and machining parameters during turning process. This is the aspect to be seriously considered and be applied in attaining sustainable machine tool development during design and development stage and its usage. This finding provides useful guidelines for manufacturers to produce high quality machined parts at minimum manufacturing cost. It was found that the cutting speed, feed rate, final part length, vibration x and vibration z have significant effects on dimensional accuracy of the machined parts.